Reinventing a Democratic Republic of Congo Free from Political Corruption - Napon, Temaizian Aline (Advances in Social Sciences Research Journal, 2025)
This article examines the enduring nature of systemic political corruption in the Democratic Republic of Congo (DRC), exploring its historical origins, institutional weaknesses, and socio-economic consequences. Despite post-2000 anti-corruption initiatives—such as the 2005 Anti-Corruption Law and the establishment of the Agence de Prévention et de Lutte contre la Corruption (APLC)—these efforts have struggled against political interference, judicial politicization, and entrenched elite resistance. Colonial legacies of exploitation, kleptocratic governance, and dependence on extractive industries have deepened corruption, redirecting resource wealth away from critical public services and perpetuating widespread poverty (62% of the population lives below the poverty line). Utilizing a narrative literature review alongside theoretical frameworks like Principal-Agent and Institutional Theories, the research contrasts the DRC’s challenges with successful anti-corruption reforms in Rwanda, Botswana, and Georgia. Key findings emphasize the critical need for political will, institutional independence, and active civil society participation. Recommendations include the creation of an independent anti-corruption court, adoption of blockchain-based transparency mechanisms, enforcement of international accountability for extractive industries, and economic diversification through sovereign wealth funds. The study advocates for transformative governance reforms to shift from predatory practices to public service-oriented systems, providing a strategic framework for equitable development in resource-rich, post-conflict settings.